THE ASYMMETRIC VOLATILITY OF THE ISLAMIC CAPITAL MARKET DURING THE COVID-19 PANDEMIC - Nurdany, Achmad; Ibrahim, Muhammad Hanif; Romadoni, Muhammad Fathul (Journal of Islamic Monetary Economics and Finance, 2021)
This study attempts to identify the existence of asymmetric volatility in the Islamic capital market in Indonesia during the Covid-19 pandemic. The paper employs the symmetric analysis of the GARCH (1,1) model and the asymmetric analysis of the TGARCH (1,1) model in order to identify Islamic capital market behaviour during the first 200 days after the first Covid-19 cases were confirmed. We used the daily closing prices of the Indonesia Sharia Stock Index (ISSI). The symmetric analysis of the GARCH (1,1) model revealed that the current value of return on the ISSI does not have a significant impact on its future value. On the other hand, the TGARCH (1,1) model showed that the asymmetric parameter coefficient was positive and statistically significant. Good news and bad news does not have the same level of impact on the volatility of returns on the ISSI. Furthermore, coefficients αi and γi in the variance equation indicate that good news has a higher volatility impact than bad news. The results indicate that investors should not to worry about the bad news effect of the Covid-19 pandemic, while the government should continue the mitigation of the spread of the coronavirus along with its economic recovery policy.